W' reconstitution modelling during intermittent exercise performed to task failure - Welburn, A. J.; Pugh, C. F.; Bailey, S. J.; Ferguson, R. A. (European Journal of Applied Physiology, 2025)
Purpose W' balance (W'BAL) modelling is becoming an important tool to monitor intermittent cycling performance. This study assessed the ability of different time constant (tW') equations for W' reconstitution (W'rec) to predict exhaustion during intermittent exercise and the relationship between parameters of W'rec with established determinants of endurance performance.